A review of the mechanisms that confer antibiotic resistance in pathotypes of E. coli - Nasrollahian, Sina; Graham, Jay P.; Halaji, Mehrdad (Frontiers in Cellular and Infection Microbiology, 2024)
The dissemination of antibiotic resistance in Escherichia coli poses a significant threat to public health worldwide. This review provides a comprehensive update on the diverse mechanisms employed by E. coli in developing resistance to antibiotics. We primarily focus on pathotypes of E. coli (e.g., uropathogenic E. coli) and investigate the genetic determinants and molecular pathways that confer resistance, shedding light on both well-characterized and recently discovered mechanisms. The most prevalent mechanism continues to be the acquisition of resistance genes through horizontal gene transfer, facilitated by mobile genetic elements such as plasmids and transposons. We discuss the role of extended-spectrum β-lactamases (ESBLs) and carbapenemases in conferring resistance to β-lactam antibiotics, which remain vital in clinical practice. The review covers the key resistant mechanisms, including: 1) Efflux pumps and porin mutations that mediate resistance to a broad spectrum of antibiotics, including fluoroquinolones and aminoglycosides; 2) adaptive strategies employed by E. coli, including biofilm formation, persister cell formation, and the activation of stress response systems, to withstand antibiotic pressure; and 3) the role of regulatory systems in coordinating resistance mechanisms, providing insights into potential targets for therapeutic interventions. Understanding the intricate network of antibiotic resistance mechanisms in E. coli is crucial for the development of effective strategies to combat this growing public health crisis. By clarifying these mechanisms, we aim to pave the way for the design of innovative therapeutic approaches and the implementation of prudent antibiotic stewardship practices to preserve the efficacy of current antibiotics and ensure a sustainable future for healthcare.